The Effect of Teaching Picture-books on Iranian Elementary EFL Learners’ Vocabulary Learning - Arash Hashemifardnia; Ehsan Namaziandost; Fariba Rahimi Esfahani (Journal of English Language Teaching and Linguistics, 2018)
Regarding the attractiveness of picture books, this study examined the impacts of teaching picture books on vocabulary learning of 40 Iranian elementary students. The participants were randomly assigned to two groups of 20; one experimental and one control. Then, their knowledge of vocabulary was assessed through administering a researcher-made vocabulary pre-test.  After that, the researchers started to teach the experimental group through teaching picture-book of Starters Word List Picture Book. The words were taught to the students and they were required to match each word with its picture. The control group was instructed through their school textbook (Prospect One). The words were taught without their pictures; the words were read and simultaneously the students were wanted to repeat them and write their Persian equivalents. After the instruction ended, a vocabulary post-test was given to determine the effects of the treatment on the students’ vocabulary learning. The results of paired and independent samples t-tests indicated that the experimental group outperformed the control group on the post-test.  It was also revealed that teaching through picture books resulted in better vocabulary learning.